EFEKTIVITAS PENGAWET PADA PRODUK LOKAL EYELINER WATERPROOFTERHADAP PERTUMBUHAN Pseudomonas aeruginosadan Candida albicans YANG DIJUAL DI PASAR BLAURAN KOTA SURABAYA - Habiba M. Assegaf; Christina Avanti; Ridho Islamie (CALYPTRA, 2018)
Abstract – The purpose of this study was to test the effectiveness of preservatives on waterproof eyeliner sold in Pasar Blauran Surabaya. The method used in this research is Total Plate Numbers (ALT) using Nutrient Agar (NA) media for Pseudomonas aeruginosa and Saboraud Dextrose Agar with addition of antibiotic (SDAa) for Candida albicans to obtain a 5,6 x 108CFU / ml suspension for Pseudomonas aeruginosa and 2.0 x 107 CFU / ml for Candida albicans. Then the suspension was added to the sample, then observed the growth of bacterial colony and yeast on the 2nd and 7th day. The result obtained is no growth of Pseudomonas aeruginosa and Candida albicans on day 2 and 7, so preservative in the sample can be said to be effective in inhibiting the growth of bacteria and yeasts.